Identification of Codonopsis Radix from different origins based on odor information - Guo, Xingyu; Yang, Ruiqi; Wang, Jiayu; Wang, Yushi; Yu, Shulin; Zou, Huiqin; Yan, Yonghong (Frontiers in Nutrition, 2025)
IntroductionCodonopsis Radix, a natural plant with edible and medicinal functions, is in high demand and cultivated in different regions. The place of origin affects the quality. However, environmental factors such as soil, climate, and altitude all have an impact on its quality. Therefore, identification of geographical origins of Codonopsis Radix is very important.MethodsThis study used High Performance Liquid Chromatography (HPLC) fingerprint and Electronic Nose (E-nose) technology to identify the origin information of Codonopsis Radix. HPLC fingerprint can fully reflect characteristics of chemical components in Codonopsis Radix and provide a reliable chemical basis for identification of origins, while E-nose technology captures and analyzes volatile odor of Codonopsis Radix by simulating human olfactory system, which realizes rapid identification of origin information. In order to reveal origin of special aroma of Codonopsis Radix in a deeper way, we further employed Solid Phase Micro-extraction Gas Chromatography-mass Spectrometry (SPME-GC-MS) technique to elucidate the volatile substances of unique aroma.ResultsOdor information could replace chemical components to achieve the identification of Codonopsis Radix geographical origins and Hexanal might be a key volatile compound in Codonopsis Radix from different geographical origins.DiscussionThis research indicated that Codonopsis Radix from different origins can be identified by odor information, which not only enriched index system for quality evaluation of Codonopsis Radix, but also provided new ideas and methods for origin identification of same type of plants.